(3GddDdD GdefJNH aj PcQ CTQGa GdYQHs - (3eUWaj YHO Gddg Hf eMeO Hf eUWaj Hf YHO GdQMef Hf fYeI Gddg GMdHj GdTGaYj GdbGOQj, GdCHGQjs
(3BNQgG (B:s
(3hcGf GdaQGZ ef LeYg hJCdjag s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B253 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs